2013
DOI: 10.1002/jhet.1518
|View full text |Cite
|
Sign up to set email alerts
|

The Synthesis and Antibacterial Activity of Novel 4-Pyrrolidin-3-cyanopyridine Derivatives

Abstract: in Wiley Online Library (wileyonlinelibrary.com).2-Bromo-4-(pyrrolidin-1-yl)pyridine-3-carbonitrile obtained from 2-(1,3-bis(pyrrolidin-1-yl)allylidene) malononitrile has been used as a substrate for the synthesis of new cyanopyridine derivatives: 2-methoxy, 2-phenoxy, 2-aminoethylthio, and 2-thioxo. 4-(Pyrrolidin-1-yl)-2-thioxo-1,2-dihydropyridine-3-carbonitrile 7 in reaction with suitable alkyl and aminoalkyl halides gave respective sulfides. All synthesized compounds were evaluated for their antimicrobial a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2013
2013
2015
2015

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 19 publications
0
2
0
Order By: Relevance
“…The study reveal that lower yields of nal products (7a-d) are obtained due to steric hindrance in the course of the C-C coupling process. It is found that lower yields of products (7a-d) are offered in all cases (entries 1-4, Table 3) irrespective of the nature of substituents present on terminal alkyne substrates (5a, 5b, 5f and 5i) when 2-bromobenzandehyde (1a) is used instead of 3-bromobenzandehyde (1).…”
Section: Resultsmentioning
confidence: 95%
“…The study reveal that lower yields of nal products (7a-d) are obtained due to steric hindrance in the course of the C-C coupling process. It is found that lower yields of products (7a-d) are offered in all cases (entries 1-4, Table 3) irrespective of the nature of substituents present on terminal alkyne substrates (5a, 5b, 5f and 5i) when 2-bromobenzandehyde (1a) is used instead of 3-bromobenzandehyde (1).…”
Section: Resultsmentioning
confidence: 95%
“…Heterocyclic system containing pyridine ring, constitute an important class of potentially bioactive compounds. The earlier workers reported that, pyridine derivatives are associated with a wide spectrum of biological activities viz antimicrobial 1-2 , anti-inflammatory 3 , antibacterial 4 , anti-parkinsonian 5 , anticonvulsant 6 , analgesic 7 etc. Similarly oxadiazole have shown a wide range of applications in drug development against convulsant 8 , inflammatory 9 , bacterial [10][11] and microbial [12][13] etc.…”
Section: Introductionmentioning
confidence: 99%